Carnes y proteínas vegetales: hábitos de consumo y percepción de la población argentina. - Soteras, Trinidad; Denoya, Gabriela Inés; Vaudagna, Sergio Ramon; Szerman, Natalia; Galmarini, Mara Virginia (Latitud – Fundación LATU, 2022)
Poster